POLYPHENOL COMPOSITION OF THE FRUIT AND STEM OF ELDERFLOWER WILD-GROWING IN GEORGIA (World Science, 2022)
Extending the range of medicinal products produced from plant raw materials and great interest in herbal medicine are totally linked to the availability of plant raw materials, minor toxicity and side effects. The use of medicinal plant raw materials as a source of valuable biologically active substances in the pharmaceutical and food industries is relevant.The aim of the study was to quantify and evaluate antioxidant activity of biologically active compounds (total phenols, anthocyanins) in the fruit and stem of elderflower (Sambucis nigra) and fruits of Caucasian bilberry (Vaccinium artostaphyion) wild-growing in Georgia.As raw material under study, we used wild-growing elderflower fruit with the fruit-bearing stem and bilberry fruits collected in August 2020 in the mountainous region of Georgia (Racha-Lechkhumi) in the phase of full ripeness.It has been confirmed that the elderflower’s fruit stems, as well as the fruit of elderflower anise and bilberry are rich in: phenolic compounds (elderflower’s fruit -13.8 mg/g, stem - 9.2 mg/g; bilberry fruit - 24.9 mg/g); anthocyanins (elderflower’s fruit - 1.4 mg / g, stem - 3.68 mg/g; bilberry fruit - 18.03 mg /g); they are characterized by high antioxidant activity (elderflower’s fruit - 48.2%, stem - 40.5%; bilberry fruit - 60.3%). Based on the results obtained, the fruits of bilberry and elderflower can be considered to be a cheap alternative source of natural antioxidants for the pharmaceutical, cosmetic and food industries.